Pendekatan Dakwah Rasulullah di Era Madinah dan Relevansinya di Era Modern - Choirin, Muhammad (Faculty of Islamic Studies, University of Muhammadiyah Jakarta, 2024)
This research stems from the need to understand effective da'wah strategies for building a harmonious and just society in a modern era full of challenges such as globalization and pluralism. The primary objective of this study is to analyze the da'wah approach implemented by Rasulullah SAW during the Madinah era, which includes community building, drafting the Charter of Madinah, constructing the Nabawi Mosque, religious education, diplomatic relations, social justice, and military defense, and to evaluate its relevance in a contemporary context. The research employs a qualitative approach with historical analysis of literary sources. The results indicate that the principles of Rasulullah's da'wah, such as inclusivity, justice, solidarity, and education, remain highly relevant and can be adapted to address social challenges in the modern era. Implementing these principles can strengthen community solidarity, enhance social welfare, and improve interfaith relations in multicultural societies.